Synthesis of a novel phosphate‐containing highly transparent PMMA copolymer with enhanced thermal and flame retardant properties. (4th December 2019) - Yang, Baoping; Wang, Lurong; Guo, Yongliang; Zhang, Yabin; Wang, Niannian; Cui, Jinfeng; Guo, Junhong; Tian, Li
Abstract : A novel poly(methyl methacrylate) (PMMA)‐based copolymer (PMMA‐co‐BDPA) rich in aromatic rings was synthesized via radical copolymerization between a phosphorus‐containing acrylic monomer (BDPA) and methyl methacrylate (MMA). UV‐vis spectroscopy demonstrated that the copolymer had high transparency. Thermogravimetric analysis (TGA) and a differential scanning calorimeter (DSC) were used to test the thermal properties of the composites. Additionally, the PMMA‐co‐BDPA‐15 copolymer exhibited a 23% increase in the limited oxygen index (LOI) value. A cone calorimeter test indicated that the peak heat release rate (pk‐HRR) of PMMA‐co‐BDPA was reduced by 29.2% compared with that of pure PMMA, and the carbon yield of burning was obviously increased. The combined test results demonstrated that the prepared copolymer material had good transparency, thermal stability, and flame retardancy.